Role of meiobenthic assemblages in detritus based food chain from estuarine environment of Goa - Kulkarni, Shantanu S; Rivonker, C U; Sangodkar, U M X (Indian Journal of Fisheries, 2011)
The paper describes the variations in ecological parameters and their possiblerole on vertical distribution of meiobenthic communities in the estuarine marshyenvironment at Goa. The investigations conducted during post monsoon seasonsuggest that hydrobiological parameters are regulated by local attributessuch as land use pattern and coastal processes. Further, the variation in environmentalcharacteristics had direct relationship with meiobenthic populationdensity and its variations. Among biological parameters the sediment Chlorophylla (Chl a) was found to be closely related with meiobenthic density (r=0.89: p